Pelatihan Pemanfaatan Modal Sosial Masyarakat Lokal di Kelurahan Limau Manis Selatan Kecamatan Pauh, Kota Padang - Indah Adi Putri; Bakaruddin Rosyidi; Aidinil Zetra; Asrinaldi Asrinaldi; Tengku Rika Valentina; Tamrin Tamrin; Dewi Anggraini; Mhd. Fajri; Didi Rahmadi (Warta Pengabdian Andalas, 2019)
This paper discusses the importance of social capital in the midst of society. Social capital can be interpreted simply as a social bond. These social ties arise because of trust and social networks. In reality, this social bond has not been and is not utilized well. This dedication was carried out in the Limau Manis Selatan Village, Pauh District, Padang City. The approach used in the implementation of the community service program is a participatory Rural Appraisal (PRA) approach. In this service, several things are discovered, namely, first, social capital will be destroyed if there are no rechecks on any new developments or information. Second, social capital will be strong if the common goals are known and agreed upon by all elements of society. Third, all parties must have the same intention and motivation. Fourth, in the community there will be groups that have problems, each group has rules that must be obeyed, as long as the rules are followed, then the organization or groups will continue to run. Fifth, for community cohesiveness, must follow a joint decision. Sixth, eliminate suspicion and personal pride.